2018
DOI: 10.3390/s18020507
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Remote Depth Estimation of Buried Radioactive Contamination

Abstract: Existing remote radioactive contamination depth estimation methods for buried radioactive wastes are either limited to less than 2 cm or are based on empirical models that require foreknowledge of the maximum penetrable depth of the contamination. These severely limits their usefulness in some real life subsurface contamination scenarios. Therefore, this work presents a novel remote depth estimation method that is based on an approximate three-dimensional linear attenuation model that exploits the benefits of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Second, the proposed model yields a larger value for the maximum detectable depth. Recent studies have shown that the maximum detectable depths of 8.89-µCi Cs-137 and 0.24-µCi Co-60 buried in sand are 12 cm and 3 cm, respectively [14][15][16]. In fact, the activity intensity of the Cs-137 used in this work was about 10 times weaker than that of the Cs-137 used in those studies.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Second, the proposed model yields a larger value for the maximum detectable depth. Recent studies have shown that the maximum detectable depths of 8.89-µCi Cs-137 and 0.24-µCi Co-60 buried in sand are 12 cm and 3 cm, respectively [14][15][16]. In fact, the activity intensity of the Cs-137 used in this work was about 10 times weaker than that of the Cs-137 used in those studies.…”
Section: Discussionmentioning
confidence: 49%
“…In fact, the activity intensity of the Cs-137 used in this work was about 10 times weaker than that of the Cs-137 used in those studies. Hence, the maximum detectable depth of 21 cm for both weakly active 0.94-µCi Cs-137 and 0.69-µCi Co-60 sources buried in sand was indeed a significant improvement in comparison to existing methods [9][10][11][12][13][14][15][16]. Third, the proposed technique provided a much faster and more accurate estimation of depths up to the maximum detectable depth (i.e., 21 cm), which was achieved within 60 s, even for sources with a weak activity.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Given a radioactive source S buried inside a material at depth z as shown in Figure 1, the ratio of the intensity I (x,y,z) measured at any position (x, y) on the surface of the material to that measured from a reference position (i.e., (x, y) = (0, 0)) on the same surface is given by [20]:…”
Section: Approximate 3d Linear Attenuation Modelmentioning
confidence: 99%
“…Also, other nonintrusive methods reported in [15,16] use specialised shielding and collimator arrangements while those that employ machine learning [17][18][19] require significant amount of data to train the algorithms. Therefore, a new nonintrusive depth estimation method based on an approximate three-dimensional (3D) attenuation model was recently developed [20]. The method is simple to setup and can be used to estimate the depth of any gamma emitting radioactive source.…”
Section: Introductionmentioning
confidence: 99%